2014
DOI: 10.1080/03610926.2012.700378
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Class of Estimators for the Population Mean Using Auxiliary Information in Stratified Random Sampling

Abstract: This article addresses the problem of estimating the population mean in stratified random sampling using the information of an auxiliary variable. A class of estimators for population mean is defined with its properties under large sample approximation. In particular, various classes of estimators are identified as particular member of the suggested class. It has been shown that the proposed class of estimators is better than usual unbiased estimator, usual combined ratio estimator, usual product estimator, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Both real-life applications and simulation studies are performed to access the potentiality of the proposed estimators over the competitors. Numerical findings confirmed that the proposed estimators have the minimum mean square errors than all the other existing estimators such as usual unbiased, combined ratio, combined regression, Haq and Shabbir [7], Singh and Solanki [8] and Solanki and Singh [10,11]. Therefore, new proposed estimators under stratified random sampling are very attractive to the survey statisticians.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Both real-life applications and simulation studies are performed to access the potentiality of the proposed estimators over the competitors. Numerical findings confirmed that the proposed estimators have the minimum mean square errors than all the other existing estimators such as usual unbiased, combined ratio, combined regression, Haq and Shabbir [7], Singh and Solanki [8] and Solanki and Singh [10,11]. Therefore, new proposed estimators under stratified random sampling are very attractive to the survey statisticians.…”
Section: Discussionsupporting
confidence: 54%
“…In this section, we compare the performance of newly proposed estimators with the traditional unbiased, combined ratio and combined regression estimators and existing estimators, i.e. Haq and Shabbir [7], Singh and Solanki [8] and Solanki and Singh [10,11]. We considered a real-life data set of Turkey (2007) used by Koyuncu and Kadilar [3].…”
Section: Application On a Real Datamentioning
confidence: 99%
See 1 more Smart Citation
“…(34) 3.7. Solanki and Singh [10]. Given below is the class of estimators suggested by Solanki and Singh [10]:…”
Section: Koyuncu and Kadilarmentioning
confidence: 99%
“…Having edge of this traditional information, many authors have been trying to explore new optimal estimators and families of estimators for estimating population mean under stratified random sampling. Stratified random sampling has often proved needful in improving the precision of estimators over simple random sampling, for instance, see works of Kadilar and Cingi [1,2], Koyuncu and Kadilar [3,4], Singh and Vishwakarma [5][6][7], Shabbir and Gupta [8], Haq and Shabbir [9], Singh and Solanki [10], Yadav et al [11], Solanki and Singh [10,12], Javed et al [13], and Javed and Irfan [14].…”
Section: Introductionmentioning
confidence: 99%